Penerapan Media Pembelajaran Video Tutorial Pada Mata Pelajaran Dasar-Dasar Teknik Ketenagalistrikan - Khaira, Munzilatunil; Habibullah, Habibullah (Jurnal Pendidikan Teknik Elektro, 2024)
This research was motivated by problems found in class X TKL at SMK N 1 Bukittinggi. Based on the results of observations made, it can be seen that during the learning process students were less active, rarely asked questions or expressed their opinions and students did not develop critical thinking skills resulting in low problem-solving skills by students. To improve student this, the researcher tried to conduct research by applying video tutorial learning media to student learning outcomes in the Basics of Electrical Engineering subject at SMK N 1 Bukittinggi. Learning media is needed to support the learning process. One type of supportive learning media that is attractive to students is audio-visual media, especially video tutorial media. The advantages of video tutorial media: can be played back to increase students' understanding, will help simplify the learning process for teachers and students, make learning more interesting, effective, and efficient. This research is quantitative research using the Pre-Experimental method with a One Group Pretest - Posttest Design research design. The subjects of this research were all class X TKL students. Based on the research results, the average pretest and posttest scores were obtained using analysis using the N Gain Score in the medium category. Based on the results of calculating classical completeness after applying video tutorial learning media in the very high category. Based on the research results, it was found that the application of video tutorial learning media can improve student learning outcomes.